Wastewater Reclamation and Reuse Trends in Turkey: Opportunities and Challenges - Maryam, B.; Büyükgüngör, H. (Elsevier Ltd, 2019)
Climate change, rapid urbanization, industrialization, tourism with a huge amount of wastewater discharge means that wastewater reuse has a great potential in Turkey and reclamation and reuse is the promising candidate to conserve the valuable fresh water sources. The water reuse applications are becoming increasingly a matter of interest in Turkey however it is strongly dependent on following factors: rapid adaptation of urban wastewater reuse programs, the establishment of integrated water resources management framework and guidelines for wastewater reuse programs but on the contrary slow pace of projects, unclear or absence of water quality requirements, the limited commercial development of reclaimed water and lack of public awareness, lack of knowledge about the consequences of untreated or partially treated wastewater discharge into water bodies, difficulties in accepted planning procedures and emerging new technologies in real time scale are the main hurdles in the way of water reclamation and reuse. This paper aims to give an overview of water reuse activities in Turkey and the opportunities and challenges in expanding reclaimed water reuse. This review precisely presents the research trends performed in different institutes to meet the wastewater reuse goal along with the wastewater treatment plants currently working in Turkey. © 2017 Elsevier Ltd
Keywords: Advanced Wastewater Treatment Technologies; Micropollutants; Turkey; Wastewater Reclamation; Wastewater Reuse